A method for the rapid isolation of virus from cultured cells - Byung-Whi Kong; Linda K. Foster; Douglas N. Foster (BioTechniques)
A simple and efficient collection method using hypotonic burst to isolate virions from infected cultured cells is described. Distilled water treatment of avian metapneumovirus (AMPV)-infected cells with thorough mixing and repeated pipeting was considerably faster for virion collection in avian cells compared to the widely used freeze-thaw (F-T) method (30 min vs. 3–4 h). This method was also more effective for virion collection. The total number of virions recovered from AMPV-infected immortal turkey turbinate cells by the novel water lysis method was 3-fold higher than by the F-T method. This simple water lysis method can be applied to virion collection for other RNA viruses such as the paramyxoviruses that are used to infect cultured cells.